Influences of Native Oxide on the Properties of Ultrathin Al2O3‐Interfaced Si/GaAs Heterojunctions. Issue 13 (7th March 2022) - Hasan, Md Nazmul; Zheng, Yixiong; Lai, Junyu; Swinnich, Edward; Licata, Olivia Grace; Baboli, Mohadeseh A.; Mazumder, Baishakhi; Mohseni, Parsian K.; Seo, Jung‐Hun
Abstract: The structure property of non‐ideal Si/GaAs heterostructures that are integrated with the ultra‐thin oxide (UO) tunneling interfacial layer is systematically investigated. Si nanomembranes (NMs) are oxidized in different time periods prior to the hetero‐integration process to create the non‐ideal single‐side passivated Si/GaAs heterostructure. The atomic‐level oxygen distribution and the degree of oxygen content in Si NM and GaAs are carefully investigated using atom probe tomography (APT) and X‐ray photoelectron spectroscopy (XPS) to trace changes in the chemical composition and reactional mechanism across the UO interface when the surface of Si NM is exposed to air for different periods of time. The negatively induced charges at the UO layer cause oxygen diffusion to the GaAs layer and form the unwanted GaAs oxide layer. This native oxide stack noticeably degrades the thermal properties of the Si/GaAs heterostructure as Si NMs become more oxidized. This study reveals that the poor surface passivation on one side of the heterointerface leads to a both‐side oxidation, thus severely deteriorating the transport properties across the heterojunction formed with the UO layer. Abstract : The structure property of non‐ideal Si/GaAs heterostructures that are integrated with the ultra‐thin oxide (UO) tunneling interfacial layer has been systematically investigated. This study demonstrates that for semiconductor grafting‐related heterogeneous heterojunction fabrications that involve GaAs, maintaining native oxide‐free conditions at the interface is essential and critical to achieving epitaxy‐like heterojunctions.